Tsunami Run-Up Model And Inundation Maps For Malaysia - Tan, Wai Kiat (2017)
This study mainly aims to assess the vulnerability of Malaysian coasts to tsunamis originating from nearby subduction zones, namely the Sunda Trench and the Manila Trench, and from the Brunei Slide. For this purpose, a two-dimensional tsunami run-up model, codenamed TUNA-RP, is developed and validated against a standard set of benchmark problems. Model simulations are performed to produce the inundation maps for the affected Malaysian coasts for tsunamis originating from the Sunda Trench, the Manila Trench and the Brunei Slide. Inundation maps often serve as the basis for authorities and local communities to plan evacuation route and manage coastal development.